Mobsters are human too: behavioural science and organized crime investigation - Duyne, Petrus C. van (Crime, law and social change, 2000)
The paper describes the organized criminal, and the fight against organized crime from a behavioural point of viiew. The author considers the organized criminal a crime-entrepreneur who has to operate in an enduring violent entrepreneurial landscape in which he has to cope with the problem of social information management. The article described how the police can add a social psychological approach to the traditional investgative methods. I provides some experience obtained in the Netherlands in which the psychologist assisted the crime squad during the investigation, trial preparation and trial. It argues in favour of a more analytical, hypothesis testing method in whch the behavioural scientist is integrated in the operational organized crimesquad instead of acting as an outside consultant.